Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1080/0886022x.2017.1419970
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, characteristics and prognosis of acute kidney injury in Cameroon: a prospective study at the Douala General Hospital

Abstract: Objective: There are limited data on AKI in sub-Saharan Africa. We aim to determine the incidence, characteristics and prognosis of AKI in Cameroon.Patients and methods: A prospective study including all consenting acute admissions in the internal medicine and the ICU of a tertiary referral hospital in Cameroon from January 2015 to June 2016. Serum creatinine assay was done on admission, days 2 and 7 to diagnose AKI. For patients with AKI, serum creatinine was done on discharge, days 30, 60 and 90. AKI was def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 45 publications
5
31
3
Order By: Relevance
“…Yearly, acute kidney injury (AKI), a sudden deterioration in kidney function, affects more than 13 million people globally leading to almost 2 million deaths. [1][2][3] Almost 80% of the AKI burden occurs in low-and middle-income countries (LMIC). 1,3 The incidence of AKI varies according to geographical location, etiological factors, and health resources; however, AKI is significantly higher in LMIC such as sub-Saharan Africa (SSA) 1 and is linked with longer hospital stay, higher hospital, and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Yearly, acute kidney injury (AKI), a sudden deterioration in kidney function, affects more than 13 million people globally leading to almost 2 million deaths. [1][2][3] Almost 80% of the AKI burden occurs in low-and middle-income countries (LMIC). 1,3 The incidence of AKI varies according to geographical location, etiological factors, and health resources; however, AKI is significantly higher in LMIC such as sub-Saharan Africa (SSA) 1 and is linked with longer hospital stay, higher hospital, and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Among AKI patients, the RRT rate was 13% in our study. Other studies reported RRT rates of 7.3% 23 , 10.2% 22 and 36.5% 8 . The need for RRT is one of the main complications of AKI and has a strong association with failed recovery of renal function and a high mortality rate; many aspects of RRT have sparked controversy 28 .…”
Section: Discussionmentioning
confidence: 95%
“…In a single-centre prospective study, Halle et al . 23 analysed 2,402 critically ill African patients, and the overall incidence of AKI according to the KDIGO criteria was 22.3%.…”
Section: Discussionmentioning
confidence: 99%
“…Nephrotoxic AKI was observed in 14.5% of the elderly and was mainly due to use of aminoglycoside and herbal remedies. Nephrotoxicity is linked to 10% -20% of AKI in Cameroonian studies [14] [15] [23]. However, Yao et al, found a lower frequency of nephrotoxic AKI in the elderly (2.8% vs 17%) compared to young adults [11].…”
Section: Discussionmentioning
confidence: 99%